Thermodynamic Peculiar Features of Steam Flow in Heat Pipe-Line - B. M. Khroustalev; V. D. Akeliev; V. D. Sizov; I. M. Zolotareva (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains results of the investigations pertaining to thermodynamic steam characteristics of the operating pipe-line, analysis of steam flow regimes, influence of heat losses on temperature fall along the length. The eh-diagram presents changes in e and e values which are caused by decrease of mean temperatures with the given pressure value at pipe-line inlet and outlet. The paper shows that steam enthalpy at the pipeline outlet depends on inlet enthalpy, ambient temperature and entropy difference.The constructed nomograph makes it possible to forecast steam temperature fall in the pipe-line with the purpose to ensure more efficient usage of its thermodynamic potential.